2017
DOI: 10.12783/dtetr/apetc2017/11123
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Wear of Al2O3 Ceramic Tools when Cutting Materials Based on Thermodynamics

Abstract: ABSTRACT Cutting temperature always highly reaches over to 1000℃ when high speed machining with PCBN tools. Diffusion of tool material element may have important influence on tool wear at such high temperature, the diffusion wear and oxidation wear have become the major wear mechanism. In this paper, the rules of diffusion wear and oxidation wear for PCBN cutting tools are proposed and analyzed based on thermodynamics theory. Dissolution concentrations in typical normal workplace materials of PCBN tool materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Experiment showed that with the increase in the cutting speed, carbide cobalt element will decompose into tungsten and carbon diffusing to the steel when cutting temperature is over 800 °C, which makes the tool wear exacerbation. 30…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Experiment showed that with the increase in the cutting speed, carbide cobalt element will decompose into tungsten and carbon diffusing to the steel when cutting temperature is over 800 °C, which makes the tool wear exacerbation. 30…”
Section: Experiments and Discussionmentioning
confidence: 99%